GLOBAL INFLATION AND CHANGES IN THE MONETARY POLICY INTEREST RATES OF THE CENTRAL BANKS OF THE ECONOMIES OF THE US, EUROPEAN UNION AND PERU - Morales Romero, Juan Roberto (2023)
Objective: Analyze and describe the evolution of inflation and monetary policy interest rates of the central banks of the economies of the US, the European Unión and Perú in the context of global inflation. Methods: The research approach is quantitative of a longitudinal, documentary, descriptive and comparative type with information from the CPI and monetary policy interest rates of the economic activity of the US, the European Union and Peru from January 2021 to December 2022 from sources official and private high schools. Results: Regarding the economies of the US, the European Union and Peru, a direct and positive relationship was found between the interannual inflation rate and the interest rates of monetary policy in the context of high global inflation rates with a significant coefficient of Positive asymmetry in the interest rates of the monetary policy of the FED, the ECB and the BCRP with the annualized inflation rates of the study economies. Conclusions: The restrictive monetary policy of the central banks (FED, ECB and BCRP) consisting of aggressive and gradual increases in their monetary policy interest rates are intended to reduce the year-on-year inflation rate to the price stability goal compared to to an unanchoring of inflation expectations in a scenario of global inflation due to exogenous or demand factors.